TRANSLATION SHIFTS IN THE INDONESIAN SUBTITLES OF THE ANIMATED FILM "THE JOURNEY” - Ulinnuha, Aulia; Zarkasi (Journal of Arabic Language and Literature (ALLAIS), 2025)
This study investigates the application of J.C. Catford's translation shifts in the Indonesian subtitles of the animated film "The Journey," a collaborative project between Japan and Saudi Arabia that depicts historical events in Mecca before the birth of Prophet Muhammad (PBUH). Using a descriptive qualitative approach, we analyzed various linguistic units such as words, phrases, clauses, and sentences from the film's subtitles to identify structure shifts, class shifts, unit shifts, and intra-system shifts. The primary objective was to assess how these shifts maintain semantic and syntactic integrity while ensuring the translation remains coherent and contextually appropriate. The findings reveal that structure shifts were the most frequent, accounting for 58% of the total shifts, followed by unit shifts (23%), class shifts (11%), and intra-system shifts (9%). These shifts were essential in adapting the subtitles to the grammatical and cultural norms of the target language (TL). The study contributes to the field of translation studies by providing practical insights and guidelines for translators, emphasizing the importance of using appropriate translation techniques to bridge linguistic and cultural gaps. Ultimately, the research enhances understanding and appreciation of translated animated films among diverse audiences.